Applications of Bioinformatics to Plant Biotechnology - Gomez Casati, Diego Fabian (2017)
Bioinformatics encompasses many tools and techniques that today are essential for all areas of research in the biological sciences. New databases with a wealth of information about genomes, proteins, metabolites, and metabolic pathways appear almost daily. Particularly for scientists who carry out research in plant biology, the amount of information has multiplied exponentially due to the large number of databases available for many individual plant species. In this sense, bioinformatics together with next-generation sequencing and ‘omics’ approaches, can provide tools for plant breeding and the genetic engineering of plants. In addition, these technologies enable a better understanding of the processes and mechanisms that can lead to plants with increased tolerance to different abiotic stress conditions and resistance to pathogen attack, as well as the development of crop varieties with improved nutritional quality of seeds and fruits.